145 Risk Stratification in Hypertrophic Cardiomyopathy: Evaluation of the European Society of Cardiology Sudden Cardiac Death Risk Scoring System. (3rd June 2016) - Leong, Kevin Ming Wei; Chow, Ji-Jian; Ng, Fu Siong; Yates, Sian; Wright, Ian; Luther, Vishal; David, LeFroy; Qureshi, Norman; Koa-Wing, Michael; Whinnett, Zachary; Linton, Nicholas W; Davies, David Wyn; et al.
Abstract : Introduction: Implantable cardio-defibrillators (ICDs) have proven benefit in treating lethal ventricular arrhythmias and preventing sudden death (SD) in hypertrophic cardiomyopathy (HCM), making risk stratification essential. We retrospectively evaluate the effectiveness of the 2014 European Society of Cardiology (ESC) risk scoring system in our cohort of HCM patients. Methods: We evaluated the ESC risk scoring system which employs mathematical and statistical modelling of 7 disease variables to predict SD risk over 5 years, with a recommendation for ICD implant if SD risk ≥6%. From our cohort of HCM patients previously evaluated at our centre, we retrospectively calculated the ESC 5 year SD risk score at point of implant and measured it against ICD outcome. Decision of ICD implant, prior to the introduction of the ESC scoring system, was based on clinical history and number of conventional risk markers as defined by the American College of Cardiology and Heart Association. Results: 52 out of 199 HCM patients (mean age 51 ± 13 yrs) underwent ICD implantation for primary prevention, with 8 (15%) having appropriate therapy for sustained ventricular tachycardia/fibrillation (VT/VF) over an average follow up period of 6.2 ± 4.9 yrs. There was no difference in the ESC risk scores between patients with or without device therapy (4.79% ± 1.5 vs 5.37% ± 3.3, p = 0.68) (Table 1 ). 5 of 8 (62%) patients with appropriate therapies for VT/VF had scores ranging from 3.08–5.05% and would not have reached the threshold for an ICD recommendation. In two an ICD would not be recommended and may be considered in the other three. Conclusion: The current ESC scoring system potentially leaves many high-risk patients unprotected or with ambiguous ICD implant guidance. Lowering the current threshold may improve accuracy.